Genetic diversity in cultivars and landraces of common bean based on RAPD markers analysis - Emygdio, Beatriz Marti; Antunes, Irajá Ferreira; Nedel, Jorge Luiz; Choer, Eva (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to characterize the genetic diversity within and among cultivars and landraces of common bean from RAPD markers analysis, and to evaluate the capacity of this markers in clustering common bean genotypes according to domestication centers and seed color. Thirty five common bean genotypes including 13 commercial cultivars and 22 landraces, from State of Rio Grande do Sul, Brazil, were evaluated. Genetic distances were calculated using Sorensen-Dice's similarity coefficient, displayed in a dendrogram. RAPD markers were efficient in separating cultivars and landraces according to domestication centers, but not according to seed color. Mesoamerican commercial cultivars and landraces have been clustered in different groups. A high degree of similarity was observed among cultivars in use in Rio Grande do Sul.